Green Preparation of CNTs/Graphite Supported NiFe Carbonate Hydroxides for Oxygen Evolution Reaction. Issue 18 (14th July 2022) - Liu, Yang; Wang, Yangchen; Wen, He; Han, Yuqi; Deng, Shuwei
Abstract: Developing durable and highly active non‐noble electrocatalysts for oxygen evolution reaction (OER) is highly desirable for water splitting. Herein, we report a NiFe carbonate hydroxides embedded in a carbon nanotubes and graphite composite material (NiFe CHs‐CNT/G) by a facile and green precipitation method. The NiFe CHs are in‐situ grown on CNT/G using NH3 ⋅H2 O as precipitant and CO2 in air as the source of CO3 2− under room temperature and pressure. The introduction of CNT/G not only improves the conductivity of material, but also enhances the combination of CNT/G and NiFe CHs nanosheets, thereby accelerating the transfer of electrons and reactants. Meanwhile, the catalyst with a special sandwich morphology provides larger active area to expose more active sites. Moreover, the effective interaction within the Ni and Fe in NiFe CHs‐CNT/G is benefiting for improving OER performance. All these lead to the optimized NiFe CHs‐CNT/G catalyst delivers an outstanding OER performance with a low overpotential of 300 mV at 10 mA cm −2 and a small Tafel slope of 60.13 mV dec −1 . Abstract : Electrocatalysis : We reported a NiFe carbonate hydroxides embedded in a composite carbon material consisting of acid‐treated carbon nanotubes and graphite powder (NiFe CHs‐CNT/G) by a precipitation method at room temperature. The NiFe CHs‐CNT/G exhibits excellent OER activity with a low overpotential of 300 mV at 10 mA cm −2 and a small Tafel slope of 60.13 mV dec −1 .